Local business environment, managerial expertise and tax corruption of small- and medium-sized enterprises - Nam Hoang Vu; Tuan Anh Bui; Nguyen Ngoc Minh; Ngoc Hiep Luu (Baltic Journal of Economics, 2021)
While tax corruption is widespread in many countries with inferior business environments, it is unclear how the characteristics of taxpayers influence their tax behaviour. This study investigates the impact of manager expertise on firms' tax corruption in a transition economy. Using a longitudinal dataset consisting of small- and medium-sized enterprises in Vietnam over the period from 2005 to 2015, we find that firms which are managed by more able managers are more likely to engage in tax corruption and are willing to offer higher amounts of bribe payments. We also find that improving the quality of the local business environment is associated with lower tax corruption. When the quality of the local business environment is improved, managers with greater knowledge of existing laws and regulations, and more working experience, engage less in tax corruption. Our findings imply that improving the quality of the local business environment is important for reducing tax corruption in transition economies.
Keywords: 330; local business environment; managerial expertise; SME; Tax corruption; Vietnam